Electrical safety in low voltage distribution systems up to 1 000 V a.c. and 1 500 V d.c. Equipment for testing, measuring or monitoring of protective measures. Combined measuring equipment for testing, measuring or monitoring of protective measures Part 10, (31st July 2013) - British Standards Institution
No abstract available